2006
DOI: 10.1158/0008-5472.can-05-2519
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hypoxia-Inducible Factor (HIF)-1α versus HIF-2α in the Regulation of HIF Target Genes in Response to Hypoxia, Insulin-Like Growth Factor-I, or Loss of von Hippel-Lindau Function: Implications for Targeting the HIF Pathway

Abstract: Overexpression of hypoxia-inducible factors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
240
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 318 publications
(266 citation statements)
references
References 39 publications
25
240
0
1
Order By: Relevance
“…Fukuda et al [13] suggested that IGF-I treatment increased the expression of HIF-1α in HCT116 human colon carcinoma cells, and Slomiany and Rosenzweig [37] demonstrated that IGF-I stimulates HIF-1α expression in human retinal pigment epithelial cell lines. Similarly, IGF-I has been reported to induce HIF-1α expression in human retinal epithelial cells [38] and MCF-7 breast carcinoma cell lines [3]. Therefore, to investigate the role of IGF-I in HIF-1α expression in mouse blastocysts, this study analyzed HIF-1α protein expression and localization following treatment with IGF-I.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fukuda et al [13] suggested that IGF-I treatment increased the expression of HIF-1α in HCT116 human colon carcinoma cells, and Slomiany and Rosenzweig [37] demonstrated that IGF-I stimulates HIF-1α expression in human retinal pigment epithelial cell lines. Similarly, IGF-I has been reported to induce HIF-1α expression in human retinal epithelial cells [38] and MCF-7 breast carcinoma cell lines [3]. Therefore, to investigate the role of IGF-I in HIF-1α expression in mouse blastocysts, this study analyzed HIF-1α protein expression and localization following treatment with IGF-I.…”
Section: Discussionmentioning
confidence: 99%
“…The α-subunit is hydroxylated at conserved prolyl and asparaginyl residues and targeted for degradation by the von Hippel-Lindau (VHL) ubiquitin E3 ligase complex under normal oxygen conditions. In response to low levels of oxygen, HIF-1α becomes activated and dimerizes with a constitutively expressed HIF-1β, and the complex binds to cis-acting hypoxia response elements in the promoter of target genes, which eventually regulates many cellular activities involved in oxygen homeostasis [3,4,11,[29][30][31]. Consistent with this, Harvey [7,32] suggested that HIFs may be involved in molecular mechanisms which respond to changes in oxygen status during embryo development by expressing genes of HIF-1α, -2α, and -1β subunits in mouse and bovine blastocysts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In renal cell carcinoma cells, VHL also downregulates NF-kB activity by suppressing NF-kB target anti-apoptotic genes such as FLICE inhibitory protein (c-FLIP), survivin, inhibitor of apoptosis-1 (IAP-1) and c-IAP-2, which sensitizes cells to tumor necrosis factor-induced cytotoxicity (Qi and Ohh, 2003). Importantly, VHL has been shown to downregulate the hypoxia-inducible factor (HIF) by targeting HIF-1a subunit for polyubiquitinylation and proteasomal degradation, resulting in inhibit diverse growth factor involved in renal cyst formation and angiogenesis, such as transforming growth factor-a, vascular endothelial growth factor, platelet-derived growth-factor B chain and IGF-1 (Kaelin, 2002;Carroll and Ashcroft, 2006). Although the mechanism of inhibition of NF-kB and IGF-1R by VHL are well documented, it is not fully understood how the loss of VHL induces the activation of NF-kB and the level of expression of IGF-1R.…”
Section: Introductionmentioning
confidence: 99%